Safety and Immunogenicity of EBA-175 RII-NG Malaria Vaccine Administered Intramuscularly in Semi-Immune Adults: A Phase 1, Double-Blinded Placebo Controlled Dosage Escalation Study. - Kwadwo A Koram (PLoS ONE, 2016)
The erythrocyte binding antigen region II (EBA-175 RII) is a Plasmodium falciparum ligand that mediates erythrocyte invasion and is considered an important malaria vaccine candidate. A phase Ia trial in malaria naïve adults living in the United States found the recombinant non-glycosylated vaccine antigen, EBA-175 RII-NG adjuvanted with aluminium phosphate to be safe, immunogenic and capable of inducing biologically active antibodies that can inhibit parasite growth in vitro. The aim of the current study was to assess the safety and immunogenicity of this vaccine in malaria exposed semi-immune healthy adults living in a malaria endemic country, Ghana. In this double-blinded, placebo controlled, dose escalation phase I trial, eighteen subjects per group received ascending dose concentrations (5 μg, 20 μg or 80 μg) of the vaccine intramuscularly at 0, 1 and 6 months, while 6 subjects received placebo (normal saline). The primary end point was the number of subjects experiencing Grade 3 systemic or local adverse events within 14 days post-vaccination. Serious adverse events were assessed throughout the study period. Blood samples for immunological analyses were collected at days 0, 14, 28, 42, 180 and 194. A total of 52 subjects received three doses of the vaccine in the respective groups. No serious adverse events were reported. The majority of all adverse events reported were mild to moderate in severity, with local pain and tenderness being the most common. All adverse events, irrespective of severity, resolved without any sequelae. Subjects who received any of the EBA-175 RII-NG doses had high immunoglobulin G levels which moderately inhibited P. falciparum growth in vitro, compared to those in the placebo group. In conclusion, the EBA-175 RII-NG vaccine was safe, well tolerated and immunogenic in malaria semi-immune Ghanaian adults. Its further development is recommended.ClinicalTrials.gov. Identifier: NCT01026246.